Decadal Variation in the Land Use and Land Cover Pattern of Madi, Chitwan from 1989 to 2017 with Flood Hazard Mapping - B. Adhikari; P. Pokhrel; Y. Pradhan; A. Ulak (International Association of Lowland Technology, 2020)
Land use and Land cover changes are accelerated through anthropogenic undertakings, inviting natural calamities such as floods and landslides more frequently. Madi, covering an area of about 219 km² and being a part of Chure range of Terai, is subject to rampant exploitation by human leading to major flood events in Madi (Reu Khola) almost every year. The present study deals with land cover dynamics, flood hazard assessment of Madi along with dynamics of Reu Khola from the year 1989 to 2017. GIS and RS were used to evaluate our objectives. Decadal LANDSAT images and ALOS PALSAR DEM were classified using Interactive Supervised Classification. Subsequently, each image was classified into five class viz. water bodies, forest, bare land, cultivated land and floodplain. Throughout the span of 28 years, the change in the land features of Madi can be considered quite humble compared to that of the urbanizing areas. The flood hazard map created using multicriteria decision analysis is one of a kind for that region showing how the geospatial techniques could be of great help in making developmental policies, identifying the areas prone to floods. The study of sinuosity of the banks of the Reu Khola showed significant meandering and winding of the river channel which, in the future, will help predict the nature and path of the flowing river.